2009
DOI: 10.1111/j.1600-0463.2008.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor volume of colon carcinoma is related to the invasive pattern but not to the expression of cell adhesion proteins

Abstract: Tumor volume increases during growth and due to tumor progression various mutations appear that may cause phenotypic changes. The invasive pattern may thus be affected resulting in a more disorganized growth. This phenomenon might be due to mutations in the genome of the adhesion proteins, which are responsible for the structural integrity of epithelial tissue. Tumor volume was assessed in whole mount sections of 33 colon carcinomas using Cavalieri's principle. Images from the entire invasive border were captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
3
14
1
Order By: Relevance
“…In fact, a number of observations have described a decrease of E-cadherin expression in such neoplastic conditions [2,27,28], whereas other studies failed to demonstrate this finding [29,30,31]. In our study, only 4 tumors showed absence or marked reduction of E-cadherin expression in complete accordance with a recent article that observed this pattern in only 4 of 33 CRCs examined [32]. It is worth underlining that loss of E-cadherin expression was exclusively detected in the μ-protocadherin-positive set of CRCs and, therefore, it did not interfere with subcellular localization of β-catenin, which always exhibited a membranous staining in such samples.…”
Section: Discussionsupporting
confidence: 94%
“…In fact, a number of observations have described a decrease of E-cadherin expression in such neoplastic conditions [2,27,28], whereas other studies failed to demonstrate this finding [29,30,31]. In our study, only 4 tumors showed absence or marked reduction of E-cadherin expression in complete accordance with a recent article that observed this pattern in only 4 of 33 CRCs examined [32]. It is worth underlining that loss of E-cadherin expression was exclusively detected in the μ-protocadherin-positive set of CRCs and, therefore, it did not interfere with subcellular localization of β-catenin, which always exhibited a membranous staining in such samples.…”
Section: Discussionsupporting
confidence: 94%
“…These findings confirmed the data that have been previously published by our and other research groups, indicating a controversial role of E-cadherin in CRC [4,[18][19][20] The expression changes detected for some of the other cadherin superfamily members, exhibiting a down-regulated (PCDH24) or upregulated (CDH3) expression in the tumor progression process from normal colorectal mucosa to colorectal adenoma and carcinoma, have been already observed by other authors [21,22], demonstrating the reliability of our bioinformatic analysis conditions. Based on previous reports evidencing that the lack of expression of cadherin genes is rarely due to gene mutations [23] and it is more frequently the consequence of epigenetic changes [24,25] we perfomed a methylation analysis of μ-protocadherin promoter region in colorectal adenomas/carcinomas and CRC cell lines.…”
Section: Discussionsupporting
confidence: 81%
“…OCLD seals TJs and is involved in paracellular permeability . OCLD has also been implicated in nonbarrier roles, such as cell proliferation regulation, and was found to be less highly expressed in colorectal tumors than in the normal colon mucosa . The mucus layer of the colon consists of high molecular weight glycoproteins called mucins, which are synthesized mostly by goblet cells in the colon epithelium .…”
Section: Introductionmentioning
confidence: 99%
“…roles, such as cell proliferation regulation, 9 and was found to be less highly expressed in colorectal tumors than in the normal colon mucosa. [10][11][12] The mucus layer of the colon consists of high molecular weight glycoproteins called mucins, which are synthesized mostly by goblet cells in the colon epithelium. 13 One type of mucin, transmembrane mucins, is also expressed by colonocytes, 14 and, in addition to providing a physical barrier and the first layer of defense against invasive pathogens, may activate signal transduction pathways that regulate inflammation, cell differentiation, and apoptosis.…”
mentioning
confidence: 99%